PRINCIPLES BASED ON THE DEVELOPMENT OF STUDENTS' COMPETENCE IN DESIGNING MOBILE APPLICATIONS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article analyzes the pedagogical principles that are used in the process of developing the competence of students of higher education institutions regarding the design of mobile applications.